Spacialities of widening participation: Narrative of first year students receiving financial aid - Sader, S.B.; Gabela, N.P. (South African Journal of Higher Education, 2017)
The National Student Financial Aid Scheme Act of 1999 led to the establishment of a national financial aid scheme which aimed to redress past inequities and to ensure representativity and equal access for those historically excluded from accessing higher education (Republic of South Africa, 1999). A significant body of research on legislation and policy on widening participation in South African higher education exists. This paper aims to contribute to the body of knowledge on widening participation by drawing on a recent study which aimed to investigate the higher educational experiences of students from low socio-economic backgrounds. The purpose of the study was to gain insight on the spatialities of widening participation as experienced by students receiving financial aid from the National Student Financial Aid Scheme (NSFAS). This was achieved by exploring their experiences of access to and participation at one university in KwaZulu-Natal, a province with a large rural population. To this end, the study sought to investigate the educational geographies of participation and success through narrative inquiry. The study identified both academic and non-academic factors that influence students’ access to the curriculum and participation in higher education.